PERKEMBANGAN PONDOK PESANTREN BAITURRAHMAN PURBARATU DI BAWAH PIMPINAN KH KOMARUDIN ARSYAD PADA TAHUN 2001-2019 - Abdullah, Asep; Prayoga, Dian (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
This research is motivated by developments during the leadership of K.H. Komarudin Arsyad, where there have been many changes in every field in a very short time, so that this Islamic boarding school is increasingly existing and has attracted many people to send their children to this Islamic boarding school, even though in Tasikmalaya City there are already several Islamic boarding schools whose systems and programs are the same as Islamic boarding schools. It can also be seen from the increasingly complete facilities. Departing from this idea, the author wants to know the secret behind the development of the Biturrahman cottage, which can occur very quickly and quickly. So the authors take several formulations of the problem including, how is the curriculum developed, how is the development of students and teachers, how is the impact on curriculum development and how is the development of facilities and infrastructure. With the following research objectives, to determine the development of the curriculum, to determine the development of students and teachers, to determine the impact of curriculum development and to determine the development of facilities and infrastructure. The methods used are heuristics, criticism, interpretation, and historiography. Data from this study were collected by interview techniques and some from literacy sources. The results of this study provide information related to the development process of the Baiturrahman Islamic boarding school, provide information regarding leadership, policies, and changes that make the Baiturrahman Islamic boarding school experience development.